Lake water sample chemistry - Aaron F Diefendorf; Watts Dietrich; Hans H Naake; Thomas V Lowell; Megan C Corcoran (PANGAEA, 2025)
Diatom-derived highly branched isoprenoids (HBIs) are found extensively in marine sediments, but are observed in a limited number of lake sediments. To expand on this record, between 2022 and 2024, we collected lake surface sediment samples from 50 lakes in the United States of America from the Midwest and Northeast. Studied lakes capture a range in climate, water chemistry (e.g., pH, salinity, alkalinity), size, and trophic states. Lakes also vary in their diatom species compositions. Water was collected for water chemistry at three depths including the "surface" at 10 cm depth, an "integrated" surface sample, and "deep" water (2 m above sediment/water interface) when lake depth permitted. The integrated sample was designed to collect the water from the euphotic zone where phytoplankton are concentrated. Water was sampled from the euphotic zone (calculated as 2 times the Secchi disk depth) using an integrated water sampler fabricated from a 2 m long x 5.2 cm ID PVC pipe (2" nominal schedule 40 PVC pipe) fitted with a ball valve at the top. When the euphotic zone was >2 m, only the upper 2 m was sampled. When the euphotic zone intersected with the sediment/water interface, water was collected from the surface to 0.5 m above the sediment/water interface. Discrete water samples were collected at other depths using a horizontal water sampler. Water samples were analyzed for alkalinity, dissolved inorganic carbon (DIC) concentration, and DIC carbon isotopes.
In: Diefendorf, AF et al. (2025): Diatom-derived highly branched isoprenoids in lake waters and sediments [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979496